Psychological Problems in Caregivers of Stroke Patients: Scoping Review - Upami, Prakerti Tri; Handayani, Fitria; Johan, Andrew (GLOBAL HEALTH SCIENCE GROUP, 2024)
Stroke is a leading cause of disability. Previous studies revealed that most stroke survivors leave the hospital with varying degrees of disability, often accompanied by limb hemiplegia and other dysfunctions. Caregivers make an important contribution to the health and well-being of stroke patients. This is evidenced by data as much as 25-74% of stroke patients need the help and support of caregivers to assist in various daily activities and to carry out self-management strategies. There fore the purpose of this study is to identify what psychological problems experienced by caregivers of stroke patients Methods: The approach used in this article is a scoping review. The purpose of using this approach is to identify findings that have already been done and to identify gaps in the existing literature. Results: Based on the results of the selection of article searches, 1783 literature from PubMed (778 articles), sciencedirect (500 articles) and Ebsco (505 articles) from the results of the analysis of articles that can be taken according to the criteria are 7 articles. Discussion: The 7 articles were selected where there were 14 articles that were the same in the data base to be excluded and the remaining 1769 articles. Of the 1450 articles, 319 articles were excluded because they were not relevant, not original articles and theses. The screening results obtained 312 based on the title and abstract, then excluded articles because they did not fit the inclusion criteria and did not focus on the psychological problems of caregivers of stroke patients, the final selection of full text obtained 7 articles. The sudden job of being a caregiver of a spouse or family member suffering from stroke can have adverse psychological consequences. These findings illustrate the complexity of the challenges faced by caregivers in caring for stroke patients, including psychological impacts such as anxiety, depression and workload experienced by caregivers and associated factors that influence the well-being experienced by caregivers of stroke patients.